Study of Basic Concept Formulation in The Design of Vocational Training Center in Gresik Regency - Ferdy Indrairawan; Retno Hastijanti; Febby Rahmatullah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Gresik Regency, as a rapidly developing industrial area, requires a workforce with skills that meet industrial demands. However, job training facilities that can effectively bridge the gap between the education sector and the industrial sector are still not optimal. The Job Training Center (BLK) plays an important role in improving workforce competence; therefore, a design approach is needed to comprehensively accommodate these needs. This study aims to formulate the basic design concept of a Job Training Center in Gresik Regency by considering user characteristics, object characteristics (functional), and site characteristics. The method used is a descriptive qualitative approach through literature studies and regional condition analysis. The results show that the proposed basic concept is “A Space for Synergy,” which integrates people, training activities, and the industrial environment into a mutually supportive system. This concept is implemented through flexible, open, and integrated spaces, enabling an effective training process that is relevant to industrial needs.